2018
DOI: 10.21276/apalm.1627
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Of Bone Marrow Aspiration And Trephine Biopsy In Various Haematological Disorders: A Study Of 3 Years

Abstract: Background: The bone marrow examination is an essential investigation for the diagnosis and management of many disorders of the blood and bone marrow. The aspirate and trephine biopsy specimens are complementary and when both are obtained, they provide a comprehensive evaluation of the bone marrow. The present study was conducted to compare the role of trephine biopsy with bone marrow aspiration for effectively diagnosing wide spectrum of hematological diseases. Few studies have compared the relative value of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…3 Same data is proposed by Pori V in 2018, Sajjan N in 2015, Patro MK in 2018, and Kaur M in 2014. 1,2,5,19 In study done by Humphries, it was found that cases with dry tap on bone marrow aspirate showed myelofibrosis when their trephine biopsies were examined. 20 Thus, if aspirate gives a dry tap, the hematologist should not assumed that it is because of the faulty procedure, but should prompt the hematologist to examine the trephine biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…3 Same data is proposed by Pori V in 2018, Sajjan N in 2015, Patro MK in 2018, and Kaur M in 2014. 1,2,5,19 In study done by Humphries, it was found that cases with dry tap on bone marrow aspirate showed myelofibrosis when their trephine biopsies were examined. 20 Thus, if aspirate gives a dry tap, the hematologist should not assumed that it is because of the faulty procedure, but should prompt the hematologist to examine the trephine biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Similar recommendations are suggested in literature. 2,5,24,25 The diagnostic significance of one exceed the other, depending on the nature of underlying hematological disorder.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations